European Women's Letter-writing from the Eleventh to the Twentieth Centuries - Monagle, Clare (Amsterdam University Press, 2023)
This book reveals the importance of personal letters in the history of European women between the year 1000 and the advent of the telephone. It explores the changing ways that women used correspondence for self-expression and political mobilization over this period, enabling them to navigate the myriad gendered restrictions that limited women's engagement in the world. Whether written from the medieval cloister, or the renaissance court, or the artisan's workshop, or the drawing room, letters crossed geographical and social distance and were mobile in ways that women themselves could not always be. Women wrote to govern, to argue, to plead, and to demand. They also wrote to express love and intimacy, and in so doing, to explain and to understand themselves. This book argues that the personal letter was a crucial place for European women's self-fashioning, and that exploring the history of their letters offers a profound insight into their subjectivity and agency over time.